ANALISIS TINGKAT KEPUASAN PETANI JAGUNG TERHADAP PELAYANAN LEMBAGA PEMASARANNYA DI KECAMATAN LUBUK PINANG KABUPATEN MUKOMUKO - Diyahya, Irvan; Sukiyono, Ketut; Badrudin, Redy (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2016)
This research was conducted in Sumber Makmur village, Lubuk Pinang subdistrict Mukomuko District from in March 2015 by surveyed 92 corn farmers as samples. This study is aimed at investigating the performance and the benefit of an attribute services marketing institutions agribusiness in support of corn in kabupaten mukomuko and estimating satisfaction level of corn farmers to marketing institutions services in support corn agribusiness in Kabupaten Mukomuko. The purpose of the first analyzed by Importance Performance Analysis (IPA) method and the purpose of the second analyzed by Customer Satisfaction Index (CSI) method. From IPA results, it can be drawn conclusions that marketing institution 1 services aspects that need to be improved and are considered important for farmers are fast service, right and always respond to help the farmers of corn, the accuracy of scales and willingness to respect and serving officers and by prioritising the needs of farmers. Then the marketing institution 2 services aspects that need to be improved and be considered important for farmers are communicating information the quality of corn desired consumers to farmers, the ability to communicate from the officers and openness and honesty in giving information service. Corn growers were satisfied with marketing services institution 1 with CSI of 70,65 %, and to marketing institution 2 with CSI of 72,21 %.